3PC-058 Physicochemical stability of meropenem in polypropylene syringes at 41.7 mg/mL for intensive care units. (14th March 2021) - Loeuille, G; Vigneron, J; D'huart, E; Charmillon, A; Demore, B
Abstract : Background and importance: Meropenem is a broad spectrum antibiotic used to treat severe infectious. The maximum dose recommended is 6 g/day. A stability not exceeding 24 hours has been demonstrated by many research teams in different publications. Only two studies were performed at 40 mg/mL in polypropylene syringes with conflicting stability results: 4 hours and 8 hours. Meropenem is a time dependent antibiotic; its continuous administration improves its efficiency. Aim and objectives: The objective of this work was to study the stability of meropenem solutions at 41.7 mg/mL (2 g in 48 mL), diluted in 0.9% sodium chloride (0.9% NaCl) or dextrose 5% (D5W), in polypropylene syringes not protected from light, after preparation and after 4 and 8 hours at 20–25°C. Material and methods: Three syringes for each condition were prepared. At the time of analysis, one sample from each preparation was analysed by high performance liquid chromatography coupled to a photodiode array detector at 297 nm. The method was validated according to the ICH Q2 (R1). Physical stability was evaluated by visual and subvisual inspection (turbidimetry by UV spectrophotometry at 350, 410 and 550 nm, as recommended by the European Consensus Conference). pH values were measured. Results: The method was validated with an r² of 0.9999. The coefficients of variation on repeatability and intermediate precision were <2%. In 0.9% NaCl, meropenem at 41.7 mg/mL retained more than 90% of the initial concentration after 8 hours. In D5W, after 8 hours of storage, only 86.1%±0.1% of the initial concentration remained and a major colour change was also observed (yellowing). In the D5W, we detected a significant increase in absorbance at 450 and 550 nm in 8 hours. During the stability study, pH values were all between 7.55 and 7.79. Conclusion and relevance: In D5W, meropenem was unstable, with chemical and physical instability. Meropenem was stable at 41.7 mg/mL in polypropylene syringes diluted in NaCl 0.9% for 8 hours. This new stability data allows continuous administration. References and/or acknowledgements: Curti C, et al . Stability studies of antipyocyanic beta-lactam antibiotics used in continuous infusion. Pharmazie 2019. Carlier M, et al . Stability of generic brands of meropenem reconstituted in isotonic saline. Minerva Anestesiologica 2014. Conflict of interest: No conflict of interest